1986
DOI: 10.1128/jb.168.2.739-745.1986
|View full text |Cite
|
Sign up to set email alerts
|

Location of epitopes on Campylobacter jejuni flagella

Abstract: Flagella were isolated from strains of Campylobacterjejuni belonging to different heat-labile serogroups and from a strain of Campylobacter fetus, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed that the flagellin molecular weights (Mr) were approximately 62,000. The flagellins were cleaved by hydrolysis with cyanogen bromide, and sodium dodecyl sulfate-urea peptide gel electrophoresis showed that the C. jejuni flagellins were structurally similar, and differed from C. fetus flageUin. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 35 publications
5
34
0
Order By: Relevance
“…This suggests that the epitope reported by is most likely an internal epitope that only becomes accessible to antibody under denaturing conditions. Similar results were obtained in the analysis of Campylobacter flagella, where the conserved or broadly cross-reactive epitopes were predominantly internal and only immunoreactive after denaturation (Harris et al, 1987;Logan & Trust, 1986). The results of our studies suggest that the epitope for mAb 15D8 is probably surface exposed and linear, since antibody reactivity to enterobacterial flagella was obtained with either undenatured flagellar protein (ELISA) or with SDS-denatured antigen (immunoblots).…”
Section: Discussionsupporting
confidence: 70%
“…This suggests that the epitope reported by is most likely an internal epitope that only becomes accessible to antibody under denaturing conditions. Similar results were obtained in the analysis of Campylobacter flagella, where the conserved or broadly cross-reactive epitopes were predominantly internal and only immunoreactive after denaturation (Harris et al, 1987;Logan & Trust, 1986). The results of our studies suggest that the epitope for mAb 15D8 is probably surface exposed and linear, since antibody reactivity to enterobacterial flagella was obtained with either undenatured flagellar protein (ELISA) or with SDS-denatured antigen (immunoblots).…”
Section: Discussionsupporting
confidence: 70%
“…Antigenic diversity also occurs in the case of Campylobacter flagella (20,37). Consistent with the structural model for flagellin presented above, studies at the genetic level by Thornton et al (54) have shown that serotype-specific DNA probes can be constructed by using the central area of the Campylobacter flagellin coding region.…”
Section: Discussionsupporting
confidence: 55%
“…Similarity can be seen in the NH2-terminal and COOH-terminal regions but not in the central region of the sequence. From amino acids 28 to 117, R. cecicola has (8) (3,5,8,10,11,20 (8,12,26). Recent data from Homma et al indicate that in S. typhimurium the flagellin may be in a hairpin configuration with both the NH2 terminus and COOH terminus toward the interior of the flagellin filament, implying a structural role for the termini in filament assembly (7).…”
Section: G T C a G A A G G A T A G A A G T T A T G T A A A A C A A C mentioning
confidence: 99%